Letters from the editor [ lessons on journalism and life - Woo, William F. , 1936-2006; Meyer, Philip (University of Missouri Press, 2007)
"A collection of essays by the first person outside the Pulitzer family to edit the St. Louis Post-Dispatch and the first Asian American to edit a major American newspaper. William F. Woo touches on a wide range of subjects to inspire the next generation of journalists"--Provided by publisher